Molecular mechanism of insulin resistance and obesity - Kadowaki, Takashi; Hara, Kazuo; Yamauchi, Toshimasa; Terauchi, Yasuo; Tobe, Kazuyuki; Nagai, Ryozo (Experimental biology and medicine (Maywood, N.J.), 2003)
Obesity and insulin resistance have been recognized as leading causes of major health issues. We have endeavored to depict the molecular mechanism of insulin resistance, focusing on the function of adipocyte. We have investigated a role of PPARgamma on the pathogenesis of Type II diabetes. Heterozygous PPARgamma-deficient mice were protected from the development of insulin resistance due to adipocyte hypertrophy under a high-fat diet. Moreover, a Pro12Ala polymorphism in the human PPARgamma2 gene was associated with decreased risk of Type II diabetes in Japanese. Taken together with these results, PPARgamma is proved to be a thrifty gene mediating Type II diabetes. Pharmacological inhibitors of PPARgamma/RXR ameliorate high-fat diet-induced insulin resistance in animal models of Type II diabetes. We have performed a genome-wide scan of Japanese Type 2 diabetic families using affected sib pair analysis. Our genome scan reveals at least 9 chromosomal regions potentially harbor susceptibility genes of Type II diabetes in Japanese. Among these regions, 3q26-q28 appeared to be very attractive one, because of the gene encoding adiponectin, the expression of which we had found enhanced in insulin-sensitive PPARgamma-deficient mice. Indeed, the subjects with the G/G genotype of SNP276 in the adiponectin gene were at increased risk for Type II diabetes compared with those having the T/T genotype. The plasma adiponectin levels were lower in the subjects with the G allele, suggesting that genetically inherited decrease in adiponectin levels predispose subjects to insulin resistance and Type II diabetes. Our work also confirmed that replenishment of adiponectin represents a novel treatment strategy for insulin resistance and Type II diabetes using animal models. Further investigation will be needed to clarify how adiponectin exerts its effect and to discover the molecular target of therapies.